MAKNA KONTEKS DALAM CERPEN “SENYUM KARYAMIN” KARYA AHMAD TOHARI (PENDEKATAN LINGUISTIK SISTEMIK FUNGSIONAL) - Aristiani, Ani; Baehaqie, Imam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Literature is an art form studied in schools at both primary and secondary levels. One type of literary work studied at the junior high school level is the short story. Short stories often employ language that requires interpretation beyond mere structural meaning, necessitating the integration of contexts outside of the language itself. Therefore, a linguistic approach is needed to interpret short stories, one of which is Systemic Functional Linguistics (SFL). This study aims to analyzed and describe how the SFL approach interprets language within a short story. The research method used is descriptive qualitative, providing detailed and systematic explanations. The findings indicate that, contextually, the meaning of a short story can be viewed through cultural and situational contexts. Cultural context pertains to the use of words related to the culture surrounding the production of the language. Meanwhile, within the situational context, the elements of field, tenor, and mode were identified. The Field in the short story